Prevalence of human papillomavirus and it's associated risk factors among non-cervical cancer women in Selangor, Malaysia - Abdul Rahman, Nurul Asyikin (2009)
Persistent high-risk human papillomavirus (HPV) infection is known to play an important role in the carcinogenesis of cervical cancer. Since new intervention strategies namely improved HPV testing as a screening programme and HPV vaccination have been aggressively promoted in the past few years, it is crucial to discover the HPV distribution in Malaysia in order to maximize the costeffectiveness of the intervention strategy. Hence, this study was conducted to assess the pattern of HPV type distribution in Southern Selangor. This study was also conducted to determine the behavioural and sexual lifestyle as well as the socio-demographic factors that contribute to HPV infections among non-cervical cancer women in South Selangor. In this study, the efficiency of Seeplex HPV kit was also compared with nested PCR by measuring the sensitivity and also the specificity. A total of 200 cervical swab samples were collected from women attending Obstetrics and Gynecology Clinics in several hospitals in Selangor. Informed consent was obtained from each participant, who was required to answer a self-administered questionnaire regarding her socio-demographic details as well as sexual history and lifestyle. The HPV DNA was detected via nested PCR using the MY09/MY11 primers as outer primer pair and GP5+/GP6+ as inner primers that target the L1 gene of the viral genome. The PCR products were subjected to automated DNA sequencing to determine the HPV genotype. Forty samples were amplified using Seeplex HPV kit by amplification of target DNA based on DPO™ (Dual Priming Oligonucleotide) technology. Out of the 200 samples collected from March 2007 until August 2007, 84(46.7%) were detected through nested PCR as positive for HPV DNA. The most common HPV type found was type 16 (85.7%), followed by HPV type 18 (7.1%), HPV 33 (3.6%), HPV 31 (1.2%), HPV 58 (1.2%) and HPV 87 (1.2%). HPV types 16, 18, 31, 33 and 58 are high-risk types associated with development of cervical cancer,whereas HPV 87 is thought to have low to intermediate risk. The prevalence of HPV infection was found to be the highest in the 30-45 age group (58.3%),followed by <30 years old (21.4%) and >46 years old (20.2%). Patients who have spouses or partners with secondary educational level were found to have higher risk of getting HPV infections with an odds ratio of 1.5 (95% CI 0.84-2.72) compared to those with primary and tertiary educational level. Malay women were found to be more likely to get HPV infection with OR = 1.5 (95% CI 0.82-2.75) compared to Chinese and Indian. Women who were suffering from gynecological problems were also found to have 2.5 times (95% CI 1.0-6.6) higher chances of getting HPV infection as compared with women who were not suffering from any gynecological problems. This study had shown that nested PCR is highly sensitive in detecting HPV DNA even in low risk patients as compared to Seeplex HPV kit. The sensitivity and specificity of nested PCR were 100% and 83.3% respectively, whereas the sensitivity and specificity of Seeplex HPV kit was 40% and 100%.